2017
DOI: 10.1007/s10578-017-0741-0
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Reactive Aggression Subgroups in Typically Developing Children: The Role of Executive Functioning, Psychophysiology, and Psychopathy

Abstract: This study aimed to assess whether groups of aggressive children differed on psychopathic traits, and neuropsychological and neurobiological measures of prefrontal functioning consistent with the objectives of their aggression—reactive or proactive. Including 110 typically developing children (9–11 years), a latent class analysis identified a low aggression group, a high reactive aggression group, and a mixed (high reactive and proactive) aggression group. Results show high callous–unemotional traits and low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 78 publications
5
49
1
Order By: Relevance
“…Importantly, these conceptual arguments have received increasing empirical evidence in support in recent years. Indeed, positive bivariate associations have been reported between indices of emotion dysregulation (broadly defined as in the present investigation) and (a) psychopathic traits (including callous-affective traits; ; (b) different components of aggression (especially physical aggression, anger, and hostility; ; for a review, see Roberton et al, 2012); and (c) different forms of aggression (i.e., both reactive and proactive aggression; Babcock et al, 2014;Bobadilla et al, 2012;Hubbard et al, 2010;Miller & Lynam, 2006;Thomson & Centifanti, 2018, for a review, see Ireland, 2018). Of note, although the residual variance in proactive aggression (i.e., controlling for the shared variance with reactive aggression) tends to be only minimally related or unrelated to indices of emotion dysregulation, it should be emphasized that interpreting such residual correlations does not come without perils.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, these conceptual arguments have received increasing empirical evidence in support in recent years. Indeed, positive bivariate associations have been reported between indices of emotion dysregulation (broadly defined as in the present investigation) and (a) psychopathic traits (including callous-affective traits; ; (b) different components of aggression (especially physical aggression, anger, and hostility; ; for a review, see Roberton et al, 2012); and (c) different forms of aggression (i.e., both reactive and proactive aggression; Babcock et al, 2014;Bobadilla et al, 2012;Hubbard et al, 2010;Miller & Lynam, 2006;Thomson & Centifanti, 2018, for a review, see Ireland, 2018). Of note, although the residual variance in proactive aggression (i.e., controlling for the shared variance with reactive aggression) tends to be only minimally related or unrelated to indices of emotion dysregulation, it should be emphasized that interpreting such residual correlations does not come without perils.…”
Section: Discussionmentioning
confidence: 61%
“…Proactive aggression is goal-directed and predatory and has been linked to psychopathic traits and lower physiological arousal and anxiety [29][30][31]. In contrast, reactive aggression is characterized as an aggressive response to minor or perceived provocation or threat and has been associated with poor behavioral and cognitive control [32], and negative emotionality and emotion dysregulation [33,34]. Although psychopathic traits are typically associated with proactive aggression over reactive aggression, person-centered analysis has demonstrated that children and adolescents with higher levels of psychopathic traits, particularly the affective features, engage in both reactive and proactive aggression [32,35,36].…”
Section: Accepted Manuscript 12 Proactive and Reactimentioning
confidence: 99%
“…Resting respiratory sinus arrhythmia (RSA) indexes parasympathetic efference to the heart via the vagus (10th cranial) nerve [43,44], and has become a widely used index of neurobiological vulnerability to emotion dysregulation [43,[45][46][47][48]. An association between RSA and aggressive and violent behavior has been well-established [32,[49][50][51][52]. However, it seems that low resting RSA is most related to reactive aggression over proactive aggression [49,53], which is unsurprising as low RSA is considered a marker for vulnerability to emotion dysregulation.…”
Section: Neurobiological Function As a Moderatormentioning
confidence: 99%
“…In stark contrast, a reduced affective responsiveness to others' distress signals, such as fearful or sad facial expressions, appears to be a characteristic dysfunction of CD individuals with high levels of CU traits. Such a profile is thought to contribute to a repertoire of rather proactive aggressive behavior that harm other people (e.g., violence) (14,15). Thus, the latter form of CD is assumed to constitute a group of individuals with decreased emotional empathy, which involves a marked difficulty in decoding and representing the emotional states of other people.…”
Section: Introductionmentioning
confidence: 99%